SARS-CoV-2 testing among patients and healthcare professionals in an HIV outpatient clinic in Brazil - Matsuda, Elaine Monteiro; de Oliveira, Isabela Penteriche; de Campos, Ivana Barros; Ahagon, Cintia Mayumi; Castejon, Marcia Jorge; Silva, Valeria Oliveira; Manzoni, Fernanda Matsuda; López-Lopes, Giselle Ibette; Brígido, Luís Fernando de Macedo (FapUNIFESP (SciELO), 2022)
The COVID-19 pandemic in Brazil has been marked by high infection and death rates. The immune response generated by current vaccination might be influenced by previous natural infection, and baseline estimates may help in the evaluation of vaccine-induced serological response. We evaluated previous SARS-CoV-2 testing (RT-PCR), and performed rapid diagnostic tests (RDT) and high throughput electrochemiluminescence immunoassay (ECLIA) before vaccination among people living with HIV (PLWH), users of antiretroviral prophylaxis (PrEP/PEP), and healthcare professionals in an HIV outpatient clinic (HCP-HC). RDT was positive in 25.7% (95% CI: 19-33%) overall, 31.3% (95% CI: 18-45%) among PLWH, 23.7% (95% CI: 14-34%) in PrEP/PEP users and 21.4% (95% CI: 05-28%) in HCP-HC (p=0.548). Diagnostic RT-PCR testing was very limited, even for symptomatic individuals, and whereas all HCP-HC had one test perfomed, only 35% of the patients (PREP/ PEP/PLWH) were tested (p<0.0001). Adequate monitoring of post-vaccination humoral response and breakthrough infections including those in asymptomatic cases are warranted, especially in immunologically compromised individuals.
Keywords: Health care personals; HIV; PEP; PrEP; Prevalence; SARS-CoV-2